Piero Gobetti's New World : Antifascism, Liberalism, Writing - Ward, David, 1953- (Book collections on Project MUSE., 2010)
Piero Gobetti's New World is both an introduction to Gobetti's thought and an in-depth study of the three main questions on which his writings focus: the relationship between Italian history and fascism, the nature of a genuine antifascist political culture, and the crisis of Italian liberalism in his day.